Automation of the Selection of the Integrated Structures, Strategies. (2016) - Peter, Pokorný; Kuznetsov, Andrey
Abstract: The article deals with the problems of integration of modern CAD systems in production engineering systems. The solution offers automated system of choosing the optimal structure strategy, which has the lowest rate of loss of information during its migration between different CAD systems. The problem of the integration of modern CAD systems, which exists due to the presence of large amounts of diverse data formats, such as: STEP, Parasolid, ACIS, IGES, STL, etc. In order to with great confidence to predict the possible loss of information when converting and then. exchange of data between the formats you need the opinion of an expert in this field. This technology makes product design more efficient by automating processes that were once manual, such as traditional drafting. With 3D CAD, designers can also do solid modeling, creating three-dimensional representations of their products.